PREVALENCE OF GIARDIASIS IN PRESCHOOL CHILDREN OF KINDERGARTENS IN TIABAYA – AREQUIPA, PERU, 2006 - Martínez-Barrios, Elí (2011)
Giardiasisis a cosmopolitan infection, it's prevalence around the world vary between 0.5 and 50%. Its prevalence averages about 15% in Latin America's rural population. Because there is very little information on the prevalence of Giardia infection in our city, we decided to investigate giardiasis prevalence in preschool children of Tiabaya`s district kindergartens, Arequipa province, Peru. Children`s parents were interviewed and fecal samples were collected from 104 children. Samples were processed by modified Teleman technique. The prevalence of Giardia intestinaliswas 25.96%; 70.37% of samples had a single parasite and 29.63% had other parásites. Most of the cases came from rural places with inadequate rubbish elimination. Diarrhea and appetite diminution were the most common symptoms.